Modelagem espacial da mortalidade por homicídios na Região Nordeste do Brasil - Silva, Carlos Carvalho da (2022)
Introduction: Violence is a challenge for public health service, it has been seen as a social problem since the antiquity. The homicide, the biggest interpesonal expression of violence is the mainly preventable causa of death. The homicide mortality rate is considered an importante mesuration indicator for violence impact in social groups. The northeast of Brazil sufers na exarcebation of violence, in evidence murders. Objectives: To Analyse the spatial, temporal and spatiotemporal distribution patterns of mortality by homicides and its relation to social markers inside health service in the northeast cities of Brazil.Materials and methodology: Ecological study, with spatiotemporal approaches, considering the social determinants of health, carried out with secondary data on deaths from aggression occurred in the federative units among january, 2000 and december, 2019, colected from the mortality information system (SIM/DATASUS) excluding the cases with unknown or ignored city location. Socio demographic and spatial data were obtained by the Institute for Applied Economic Research and The Brazilian Intitue of Geography. The statistics made integrated the spatial, temporal and spatiotemporal analysis, besides the spatial shaping for the study of the association between the homicide mortality and social determinants. Resultados: It was registered 353.089 deaths. The predominant features of the cases in the region were: Male genres among 20 and 29 years old, brown color, low or none School level, single and the crime occured in a public thoroughfare. The mortality increased from 2000 to 2019, with a 4% annual increase of male genre and 3,57 e female genre. High risk spatial and spatiotemporal clusters were identified on the coastal coast of the states. The spatial Regression model showed the association with the social determinants, Where the factors associated to homicide mortality in ordinary people were: Gini’s Index, unemployement rate, income, education level, poor people and people in poverty vulnerable homes and spend more than an hour to get to work proportions, In this way, homicide mortality has a growing tendency in the Northeast region, primarily in vulnerable population áreas. Conclusion: The results from this study shows the contribution of spatial-temporal integrated analysis to identify high-risk areas and associated factors for homicide mortality. These public health analyzes allow identification of priority areas for evaluation or public policy formulation. High rates of aggravation were observed during the study period, with increasing time trend in all states, except in Pernambuco. High risk areas were also identified with association of socioeconomic inequality factors, and should be considered as a priority for the design and investment in health.